ENHANCING STUDENTS’ ECOLOGICAL COMPETENCE THROUGH CONTEMPORARY EDUCATIONAL APPROACHES - Jamolovna, Pulatova Gulruh (Journal of Learning on History and Social Sciences, 2025)
Objective: This study examines the relevance of ecological problems in both global and national contexts, particularly under the conditions of globalization, and explores effective educational mechanisms to address these issues. Method: The research employs a scientific analysis of current ecological challenges and evaluates educational strategies, including competency-based education, interactive techniques, project-based learning, and a "learning by doing" approach. Results: The findings highlight the importance of integrating ecological competence into educational systems and emphasize the role of modern pedagogical approaches in fostering environmental awareness among students. Novelty: This paper contributes to the field by exploring the cultivation of ecological culture within educational frameworks, focusing on how active student engagement in environmental protection can be achieved through innovative teaching methods, thus addressing the pressing need for environmental education in the face of globalization.